(untitled) (Al-Academy, 2024)
Theatrical art is considered one of the arts most connected to reality as it results from a living relationship existing between it and the ideals, values and customs in which its role in society appears. Theater arose in the embrace of myth and its structural and artistic elements became clear from the depths of the myth, and from it the necessity of theater in social life appears. It plays a major role in raising awareness, guiding, and enlightening people, as it is the most influential of the arts, and the theatrical performance is not complete without the receiving viewer, who in turn interacts with the theatrical text and the theatrical performance, as the actors embody an aspect of the human experience in front of the viewer, thus adding to his knowledge balance and influencing his performance. His psychology and behavior have changed, and his cosmic outlook and life situations have changed, and here the role of theater appears in addressing the issues of societies, as he is destined to live what a person lives in life. The goal of the research: to reveal the educational use of the evil character in school theater texts. The second chapter includes two sections: the first: the evil character, and the second: employing the evil character in the theatrical text educationally. As for the research sample, the intentional sample was adopted to serve the course of the research and its directions, and the most important results and conclusions. She emphasizes the importance of faith and goodness through her practice of ingratitude and evil. 2. The writer of the theatrical text has the ability to employ and mix the evil character with the political and social reality that the individual lives, and in it situations and events can be borrowed and adapted into the text to show the evil conditions caused by wars, destruction, and division and their impact on society